2017
DOI: 10.1590/1678-4685-gmb-2016-0312
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of RT-PCR method in samples shown to be positive for Zika virus by RT-qPCR in vector competence studies

Abstract: Tissue samples from mosquitoes artificially infected with Zika virus and shown to be positive by RT-qPCR were reexamined by RT-PCR. Using these samples we compared the two methods employed in virus RNA detection for vector competence studies. Results demonstrated that, albeit useful, RT-PCR gave false negatives with low viral loads (< 106 RNA copies/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…To perform the real-time PCR we used the QuantStudio 3 Real-Time PCR System (Thermo Fisher Scientific ®) and the cut-off Ct value was ≤39 based on different criteria, among which are CDC interpretation criteria, considering a specimen positive if primer sets showed amplification with cycle threshold (CT) values ≤38.5 [ 31 ]. Different papers have showed that Zika virus could be tested positive in human and mosquito samples with CT values of 38–39 [ 32 34 ]; and a recent paper from Salvador, Bahia, Brazil, showed that serum samples with CTs > 34 could be confirmed positive for sequencing confirming that low viral copies are common in Zika virus positive patients [ 35 , 36 ]. As positive control of ZIKV we used an isolated virus from Aedes aegypti, which was donated by the Programa de Estudio y Control de Enfermedades Tropicales (PECET) de la Universidad de Antioquia and as negative control we used RNAse free water.…”
Section: Methodsmentioning
confidence: 99%
“…To perform the real-time PCR we used the QuantStudio 3 Real-Time PCR System (Thermo Fisher Scientific ®) and the cut-off Ct value was ≤39 based on different criteria, among which are CDC interpretation criteria, considering a specimen positive if primer sets showed amplification with cycle threshold (CT) values ≤38.5 [ 31 ]. Different papers have showed that Zika virus could be tested positive in human and mosquito samples with CT values of 38–39 [ 32 34 ]; and a recent paper from Salvador, Bahia, Brazil, showed that serum samples with CTs > 34 could be confirmed positive for sequencing confirming that low viral copies are common in Zika virus positive patients [ 35 , 36 ]. As positive control of ZIKV we used an isolated virus from Aedes aegypti, which was donated by the Programa de Estudio y Control de Enfermedades Tropicales (PECET) de la Universidad de Antioquia and as negative control we used RNAse free water.…”
Section: Methodsmentioning
confidence: 99%
“…However, the diagnosis of this infection poses some difficulties due to the possible cross-reaction with other flaviviruses. 5 In terms of the neuroimaging findings, a variety of cortical malformations can be identified, including parenchymal volume reduction, alterations in the gyral pattern as well in white and gray matter, ventriculomegaly, abnormalities of the corpus callosum and cerebellum, hypoplasia and/ or atrophy of the brain stem, and diffuse calcifications. 6 In 2016, the World Health Organization reported cases of microcephaly and neurological disorders associated with ZIKV as an international public-health emergency, thereby intensifying the need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that conventional RT-PCR could detect ZIKV viral load in most of the samples, with an estimated 10 6 -10 10 RNA copies/mL. 23,30 Published studies showed strong association between microcephaly and ZIKV infection confirmed by qRT-PCR, capture IgM ELISA, or both. 21,31,32 In Brazil, 32 of 91 neonates born with microcephaly were confirmed positive for ZIKV infection by qRT-PCR or anti-ZIKV IgM ELISA with confirmation more frequent in CSF than in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that conventional RT-PCR could detect ZIKV viral load in most of the samples, with an estimated 10 6 –10 10 RNA copies/mL. 23 , 30 …”
Section: Discussionmentioning
confidence: 99%